E.B. O'Callaghan, Laws and Ordinances of New Netherland, 1638-1674, at 205 (1868); N.Y. Col. MSS, VI 207, XVI 62 - (:unkn) unknown (My University, 1665)
Ordinance Of The Director General And Council Of New Netherland To Prevent Firing Of Guns, Planting May Poles And Other Irregularities Within This Province: The director General and Council expressly forbid from this time forth all firing of Guns . . .on a penalty of 12 guilders for the first offense; double for the second offense, and for the third an arbitrary correction . . .
Keywords: DISCHARGE